Behavioral effects of environmental enrichment on male and female wistar rats with early life stress experiences - Corredor, K.; Duran, J.M.; Herrera-Isaza, L.; Forero, S.; Quintanilla, J.P.; Gomez, A.; Martínez, G. S.; Cardenas, F. P. (Frontiers in Physiology, 2022)
Exposure to adverse childhood experiences or early life stress experiences (ELSs) increases the risk of non-adaptive behaviors and psychopathology in adulthood. Environmental enrichment (EE) has been proposed to minimize these effects. The vast number of methodological variations in animal studies underscores the lack of systematicity in the studies and the need for a detailed understanding of how enrichment interacts with other variables. Here we evaluate the effects of EE in male and female Wistar rats exposed to ELS (prenatal, postnatal, and combined) on emotional (elevated plus maze), social (social interaction chamber), and memory (Morris water maze), and flexibility tasks. Our results –collected from PND 51 to 64 – confirmed: a) the positive effect of EE (PND 28 to 49) on anxiety-like behaviors in animals submitted to ELSs. These effects depended on the type of experience and type of enrichment: foraging enrichment reduced anxiety-like behaviors in animals with prenatal and postnatal stress but increased them in animals without ELSs. This effect was sex-dependent: females showed lower anxiety compared to males. Our data also indicated that females exposed to prenatal and postnatal stress had lower anxious responses than males in the same conditions; b) no differences were found for social interactions; c) concerning memory, there was a significant interaction between the three factors: a significant interaction for males with prenatal stress was observed for foraging enrichment, while physical enrichment was positive for males with postnatal stress; d) regarding cognitive flexibility, a positive effect of EE was found in animals exposed to adverse ELSs: animals with combined stress and exposed to physical enrichment showed a higher index of cognitive flexibility than those not exposed to enrichment. Yet, within animals with no EE, those exposed to combined stress showed lower flexibility than those exposed to both prenatal stress and no stress. On the other hand, animals with prenatal stress and exposed to foraging-type enrichment showed lower cognitive flexibility than those with no EE. The prenatal stress-inducing conditions used here e) did not induce fetal or maternal problems and f) did not induce changes in the volume of the dentate gyrus of the hippocampus